Beyond Administrative Duties: The Role of Conflict, Competence, and Work Motivation in Enhancing Archivists’ Performance at Universitas Pendidikan Ganesha - Putu Suadharma; Komang Krisna Heryanda; M. Rudi Irwansyah (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the influence of role conflict, competence, and work motivation on archivists’ performance at Universitas Pendidikan Ganesha. The research was conducted to understand how organizational and individual factors affect the effectiveness of archival management in higher education institutions. A quantitative research approach was employed using a survey method. Data were collected through questionnaires distributed to 76 archivists and archival staff working in various administrative units within the university. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, the research instrument was tested for validity and reliability, and classical assumption tests including normality, multicollinearity, and heteroscedasticity were conducted to ensure the suitability of the regression model. The results reveal that role conflict does not have a significant effect on archivists’ performance. In contrast, competence and work motivation have positive and significant effects on archivists’ performance. Simultaneously, role conflict, competence, and motivation significantly influence archivists’ performance, with the regression model explaining 44.4% of the variance in performance. Competence emerged as the most dominant variable affecting performance. These findings imply that improving archivists’ competence and strengthening work motivation are essential strategies for enhancing archival performance in higher education institutions. Future studies are recommended to include additional organizational and technological factors to obtain a more comprehensive understanding of archivists’ performance.